A Study on the intraocular pressure of the affected and unaffected eyes in patients with isolated cranial nerve palsies - Dikmetaş, Özlem; Voykov, Bogomil (Acta Medica, 2020)
Objective: The role of elevated intraocular pressure (IOP) in the incidence and progression of glaucoma is well known. However, the exact mechanisms of IOP regulation are still unclear. Central IOP control has been suggested, but the autonomic pathway through which it acts is not known. The aim of this study was to investigate if isolated cranial nerve (CN) palsies of the third, fourth and sixth nerves are associated with an IOP difference between the affected and the unaffected eyes. Materials and Methods: This was a retrospective study including patients diagnosed with a third, fourth and sixth nerve palsy at a single tertiary centre. We included only patients with an isolated unilateral palsy. Patients with a history of strabismus, orbital disease or neurosurgical cases were excluded. Results: The charts of 1712 patients were reviewed. Third, fourth and sixth nerve palsies were found in 469 patients, 314 patients and 929 patients, respectively. Of all patients, 190 (10.6%) were eligible for inclusion in the study. A third nerve, fourth nerve or sixth nerve palsy was present in 85 (44.7%), 65 (34.2%) and 40 (21.1%) patients, respectively. The mean IOP of the affected eyes and the unaffected eyes was not statistically significant different: 14.1 ± 3.1 mmHg vs. 14.6 ± 2.7 mmHg in the CN3 group (p=0.087); 13.6 ± 2.6 mmHg vs. 13.7 ± 2.3 mmHg in the CN4 group (p=0.69); and 14.3 ± 2.7 mmHg vs. 14.9 ± 3.3 mmHg in the CN6 group (p=0.089). There was no statistically significant difference between the mean IOP differences of the affected and unaffected eyes among the three groups (p=0.47). Conclusion: Our study demonstrated no difference in IOP between affected and unaffected eyes in patients with an isolated cranial nerve palsy. These findings are the first and important for ophthalmology practice.